The Ateneo de Manila University Microform Center an exploratory study of its operations and services to libraries - Agati, Delia Unico (1989)
This research study investigates the status of the Ateneo Microform Center, its present operations and services to other libraries. It also aims to identify problems and prospects of improving its services and also to assess its impact on its clients and users. The respondents of the study include the management, students, users (faculty, staff and researchers) who are regular clientele of the Center.